PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMA NEGERI 1 NA IX-X KABUPATEN LABUHANBATU UTARA - Nurasiah Nasution; Poltak .; Eddi Sonti; Ramlan Taufik; Mhd. Affan Daulay (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this study is whether there is an influence of participatory leadership style on the performance of teachers and employees. Is there an effect of work discipline on the performance of teachers and employees. Is there an influence of the work environment on the performance of teachers and employees. Is there an influence of participatory leadership style, work discipline and work environment on the performance of teachers and employees of SMA Negeri 1 NA IX-X in North Labuhanbatu Regency. The purpose of this study was to determine and analyze the influence of participatory leadership styles on teacher and employee performance. Effect of work discipline on teacher and employee performance. The influence of the work environment on the performance of teachers and employees. The influence of participatory leadership style, work discipline and work environment on the performance of teachers and employees of SMA Negeri 1 NA IX-X in North Labuhanbatu Regency. The sample in this study amounted to 52 people. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis.The results of this study explain that the variables of work discipline and work environment have a positive and significant effect on teacher and employee performance. The participatory leadership style variable does not have a positive and significant effect on the performance of teachers and employees. The variables of participatory leadership style, work discipline and work environment have a positive and significant effect on the performance of teachers and employees of SMA Negeri 1 NA IX-X in North Labuhanbatu Regency.